The clinical significance of the erythrocyte sedimentation rate with special reference to pulmonary tuberculosis - Wiles, Frank Joseph (South African Tuberculosis Vaccine Initiative (SATVI), 2020)
There are few subjects in medicine, about which there is more controversy than the Erythrocyte Sedimentation Rate. Some authorities place great ·reliance on test while others have discarded it as having no practical importance. There is little agreement as regards either the methods of estimation and interpretation or the clinical value of the test. This thesis will deal only with practical considerations. Theories as to the mechanism of sedimentation will not be discussed.